DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA AND STUDENT LEARNING STYLE VAR MODEL - Khoiril Nurman Haqim; Ayub Budhi Amggoro (Universitas Negeri Semarang, 2024)
This development research aims to produce android-based learning media products and VAR model student learning styles on the competency of diagnosing fuel injection system damage for XII TKRO class students of SMK Muhammadiyah 2 Semarang. This research uses the Research and Development (R&D) method with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). The research design used Two Group Pretest-Posttest Design. The results of the media product validation assessment by three media experts and three material experts received the criteria